EFFECT OF ELASTIN HYDROLYSATE ON BACTERIA AND SOME SENSORY TRAITS OF CHILLED GROUND BEEF - Ghufran M.M. Al-ghanimi; Alrubeii A. M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to evaluate the effect of elastin hydrolysates on the microbial content and sensory evaluation of ground beef refrigerated at 2°C for 12 days. The study included 10 treatments: T1 without addition, T2 addition (1000ppm/kg meat) and T3 addition (500ppm/kg meat) of elastin hydrolysates produced by the elastase enzyme (E.H.E).T4 addition (1000ppm/kg meat) and T5 addition (500ppm/kg meat) of Elastin hydrolysates produced by the collagenase enzyme (E.H.C), T6 addition (1000ppm/kg meat) and T7 addition (500ppm/kg meat)of elastin hydrolysates produced by the trypsin enzyme (E.H.T), T8 addition and (1000ppm/kg meat) T9 addition (500ppm/kg meat) of elastin hydrolysate produced by the pepsin enzyme(E.H.P) and T10 added to the antioxidant BHA (0.01) Per kg of meat. The treatments were stored cold for periods of 1, 3, 6, 9 and 12 days, and some laboratory tests were conducted on them that showed the effect of elastin hydrolysates when their effectiveness was tested against Escherichia coli Staphylococcus aureus bacteria. When hydrolysates were added to cold-stored minced beef, the lowest number of bacteria was recorded, as they decreased the logarithm. Total Plate Count TPC37, total psychrophilic count TPC4, and E.coli bacteria. Addition treatments also recorded significant increase in degrees of tenderness, flavor, juiciness, and general acceptability.